New Media from Plant Extracts for Isolation of Some Pathogenic Bacteria that Produce Protease on Linum Usitatissium Seed Powder Agar and to Identify Serratia Marcescens (Medico Legal Update, 2020)
Prepared two concentration of four new enriched media for isolation of some pathogenic bacteriaincluding Acinetobacter baumannii, Klebsiella pneumoniae, Escherichia coli, and Serratia marcescens andidentification of Serratiamarcescens that produce red pigment (prodigiosin) . The first concentration 12.5 g/lof plant extracte showed heavy growth of pathogenic bacteria on the four media . The second concentration25 g/l showed also growth of the pathogenic bacteria incubation in 37°C for 24h except on the Elettariacardemomum agar and, Fenugreek (Trigonella foenum-graecum) seeds agar. Serratia marcescens producered pigment on all the new media in both concentration . All isolates produce protease enzyme on Linumusitatissium seed agar . The result is a synthesis enrichment and inexpensive medium for different speciesof bacteria like Linumusitatissium enriched with a different materials and salt as amineral that suitable forgrowth organism without any morphological change of metabolisms feature, also identification Serratiamarcescens by produce red pigment that important in medical with a wide range of biological activities.